LIMITS OF DEFAULT AND FRAUD IN LOAN AGREEMENTS - Wijaya, Adi; Kursiswanti, Eli Tri; Liwa, Maria Ana (JILPR Journal Indonesia Law and Policy Review, 2025)
This article examines the legal boundaries between default (breach of contract) and fraud in loan agreements under Indonesian law. Although default is essentially a civil matter arising from contractual relationships, in practice, many cases are criminalized under fraud charges. The study employs a normative juridical method with a doctrinal approach, relying on statutory interpretation of the Indonesian Civil Code (Article 1320) and the Criminal Code (Article 378), supported by legal scholarship, jurisprudence, and case examples. Through qualitative analysis of primary, secondary, and tertiary legal materials, the study highlights how good faith distinguishes default from fraud, while fraudulent intent (mens rea) can shift a contractual breach into a criminal offense. The findings indicate that overcriminalization of contractual disputes risks undermining legal certainty and justice for parties. Therefore, law enforcement officials must carefully assess whether a dispute falls within the civil domain or fulfills the elements of a criminal act. This article concludes that default should remain a civil matter unless deceit and malicious intent are present from the outset of the agreement.